A pilot study on the validation of vis-screen mobile application for vision test - Abdul Mutalib, Othman; Nyi Nyi, Naing; Atif Amin, Baig (2020)
Visual impairment and blindness is a global concern. Poor awareness and late detection are the significant factors contributing to the large number of visually impaired people worldwide. The ubiquitous use of smartphone devices will enable the public to access various eye care services provided. We are developing this application based on the need for early detection to avoid further vision loss. The simple algorithm and user-friendly features will promote any layperson to use it with minimal training. This pilot study revealed the application is highly potential to be a valid and reliable tool for vision screening in the community.